2023
DOI: 10.3389/fimmu.2023.1180336
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gut microbiota and COVID-19 progression: new insights into immunopathogenesis and treatment

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has posed a global health crisis. Increasing evidence underlines the key role of competent immune responses in resisting SARS-CoV-2 infection and manifests the disastrous consequence of host immune dysregulation. Elucidating the mechanisms responsible for deregulated host immunity in COVID-19 may provide a theoretical basis for further research on new treatment modalities. Gut microbiota comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 135 publications
3
11
0
Order By: Relevance
“…When we split our COVID-19 group into those who had been administered antibiotics and those who had not, we found that, in our cohort, alpha diversity was actually increased in our untreated COVID-19 patients, while it was significantly reduced in those who had received antibiotics. Interestingly, one study found that alpha diversity too was negatively correlated with COVID-19 severity and poor prognosis ( Wang et al., 2023 ), suggesting another possible reason for the conflicting results reported in the literature. Therefore, it is possible that SARS-CoV-2 infection can have different effects on the alpha-diversity of the GM depending on how long the virus has infected the patient, and on how severe the infection is.…”
Section: Discussionmentioning
confidence: 99%
“…When we split our COVID-19 group into those who had been administered antibiotics and those who had not, we found that, in our cohort, alpha diversity was actually increased in our untreated COVID-19 patients, while it was significantly reduced in those who had received antibiotics. Interestingly, one study found that alpha diversity too was negatively correlated with COVID-19 severity and poor prognosis ( Wang et al., 2023 ), suggesting another possible reason for the conflicting results reported in the literature. Therefore, it is possible that SARS-CoV-2 infection can have different effects on the alpha-diversity of the GM depending on how long the virus has infected the patient, and on how severe the infection is.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal barrier impairment, dysbiosis of gut microbiota, and perturbation of metabolites are prevalent occurrences among individuals with COVID‐19. Extensive research has consistently shown the association between microbiota composition and the morbidity, exacerbation, and mortality rates seen in COVID‐19 patients 51–55 . The gut microbiota facilitates the assessment of sickness severity in individuals with COVID‐19 56 .…”
Section: Discussionmentioning
confidence: 99%
“…patients. [51][52][53][54][55] The gut microbiota facilitates the assessment of sickness severity in individuals with COVID-19. 56 From a mechanical standpoint, it is observed that COVID-19 disrupts the composition of gut microbiota and metabolites.…”
Section: Potential Confounding Factors and Mechanismsmentioning
confidence: 99%
“…The bidirectional regulation between the gut microbiota and host immunity may play an important role in this process. 109 In addition, SARS‐CoV‐2 may cause the disorder of gut microbiota, thereby increasing susceptibility to COVID‐19. The mechanisms by which the disturbance of gut microbiota increases susceptibility to COVID‐19 and associated symptoms are poorly understood.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%